The Impact of Violent Religious Extremism on Various Cultural Components of Pakistani Society - Shah, Syed Sibtain Hussain (Journal of Education Culture and Society, 2022)
Aim. The aim of this research paper is to investigate threats of religious extremism to the various cultural components of Pakistani society. Religious extremism has rapidly increased in Pakistan since the 1970s, but this study is particularly focused on its impact on cultural elements of the country in the post 9/11 and post-Arab Spring eras. Methods. The author applied the process tracing method of qualitative approach for examining chains of the events related to the question of the impact of religious extremism on the various cultural components of Pakistani society. The situational analysis also explored the various situations connected with threats of extremism to Pakistani culture. Results. The study identified the threats of religious extremism to a number of cultural aspects of Pakistani society, such as schooling (education), traditional literature (Sufi poetry), customary art and folk music, social cultural networking, and sports in the tribal areas and other regions in the country. Conclusion. The cultural life of a state encompasses various traits of the cultural aspect of national security. In the case of Pakistan, initially two important developments; Islamization of the country and Afghan Jihad in the 1970s both severely affected the society. Then, the eras of post 9/11 and post Arab Spring further witnessed the fast emergence of threats by religious extremists to the cultural elements in various parts of the country, including its tribal regions bordering Afghanistan, and these trends also impacted other regions of the country.